Training on Digital Marketing Techniques to Increase the Entrepreneurial Spirit of High School Students - Nur Fitriayu Mandasari; Rahmat Hasanuddin; Muhammad Ashdaq (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
This Community Service Activity was carried out at UPT SMUN 2 Campalagian, Polewali Mandar Regency by the Community Service Team of the Faculty of Economics, West Sulawesi University. Some of the problems faced by partners include the suboptimal utilization of Computer Laboratory facilities by Students, digital entrepreneurship training has never been carried out for Students, training in the use of digital technology for business has never been carried out for Students, and digital marketing technique training has never been carried out for Students. The community service method used is the implementation of training activities to increase the spirit of entrepreneurship and digital literacy for students who help manage family businesses. The participants of the activity consisted of thirty-five students who were representatives of three grade levels at SMUN 2 Campalagian. The results of this community service activity include (1) increasing the spirit of entrepreneurship and digital literacy among students at SMUN 2 Campalagian, Polewali Mandar Regency, (2) increasing understanding of the use of digital technology in supporting business activities, (3) the ability to carry out product marketing techniques through digital media.